2013
DOI: 10.1139/cjce-2012-0464
|View full text |Cite
|
Sign up to set email alerts
|

Air–water flow measurements in a flat slope pooled stepped waterway

Abstract: Word count: 6,045 words.Abstract: Air-water flows on stepped spillways were investigated experimentally in the last decades with a focus on steep slope chutes equipped with flat horizontal steps. Detailed airwater flow properties were recorded herein with three stepped geometries down a slope  = 8.9º: i.e., with flat horizontal steps, pooled steps and a combination of flat and pooled steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The amount of air entrained in the flow is a function of discharge per unit width, dynamic viscosity of water, acceleration due to gravity, flow velocity, fall height and surface tension (Felder and Chanson, 2013). A dimensional analysis using these variables produces C a as a function of the Froude number, Reynolds number ( R e ; equation (19)), Weber number ( W e ; equation (20)) or a fourth form called the liquid parameter or Morton number ( M o ; equation (21)), which is a constant for a given combination of fluid in the prototype and model (Markofsky and Kobus, 1978).…”
Section: Limitations and Future Scope For Researchmentioning
confidence: 99%
“…The amount of air entrained in the flow is a function of discharge per unit width, dynamic viscosity of water, acceleration due to gravity, flow velocity, fall height and surface tension (Felder and Chanson, 2013). A dimensional analysis using these variables produces C a as a function of the Froude number, Reynolds number ( R e ; equation (19)), Weber number ( W e ; equation (20)) or a fourth form called the liquid parameter or Morton number ( M o ; equation (21)), which is a constant for a given combination of fluid in the prototype and model (Markofsky and Kobus, 1978).…”
Section: Limitations and Future Scope For Researchmentioning
confidence: 99%
“…Among them, Felder and Chanson (2013) and Thorwarth (2009) conducted physical experiments on pooled stepped spillways with chute slopes of = 8.9°, 14.6°, and 26.8°, and the results showed that the energy dissipation efficiency of pooled stepped spillways performed well, but unstable free surface fluctuations occurred at a chute slope of 8.9°, which could cause some potential problems for the step structure. Moreover, a new type of pooled stepped spillway which has a pool on the horizontal step face of every second step was also proposed, and its flow characteristics were investigated by several researchers [ 9 , 10 , 11 ]. Several experimental studies have been conducted to analyze the flow pattern of pooled stepped spillways, and the corresponding step spillway parameters in these studies are presented in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Eguchi and Tanaka investigated that an intermediate-type weir profile was employed, and it allowed to store the water for some levels and released beyond a certain limit [3]. Felder and Chanson identified that the spillway flow is of great concern in not only dam but also in many fields including chemical engineering for uniform reactor cooling [4]. e flow pattern of the fluid should ensure no flow separation to avoid air entrapment as experimented by Ghare et al [5] and Hubert et al [6], 2010.…”
Section: Introductionmentioning
confidence: 99%